Kemampuan Pemecahan Masalah Matematika dalam Menyelesaikan Soal Setara PISA Ditinjau dari Gaya Kognitif Siswa - Widya Puspita Putri; Sri Subarinah; Tabita Wahyu Triutami (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study aims to describe students’ mathematical problem-solving abilities in solving PISA-like problems based on the Field Dependent (FD) and Field Independent (FI) cognitive styles. This research employed a qualitative descriptive design. The subjects of the study were 40 students of class VIIIC at SMP Negeri 2 Mataram in the 2025/2026 academic year, consisting of 20 FD students and 20 FI students. Furthermore, six students, comprising three FD students and three FI students, were selected as interview subjects through purposive sampling. The data were collected using a cognitive style test, namely the Group Embedded Figures Test (GEFT), a mathematical problem-solving test in the form of PISA-like problems, and interview guidelines. Data analysis was conducted based on the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while also referring to Polya’s four stages of problem solving. The results of the study indicate that: (1) FD students were generally able to perform three stages of Polya’s problem-solving process, namely understanding the problem, devising a plan, and carrying out the plan. However, FD students were generally unable to perform the looking back stage; (2) FI students were generally able to perform all four stages of Polya’s problem-solving process, namely understanding the problem, devising a plan, carrying out the plan, and looking back. The findings of this study are expected to serve as a consideration for teachers in designing mathematics instruction that is aligned with student’s cognitive style characteristics.